2016
DOI: 10.15570/actaapa.2016.12
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of 5% minoxidil topical foam in male pattern hair loss treatment and patient satisfaction

Abstract: Introduction:Male pattern hair loss is widespread around the world. Its prevalence indicates the importance of finding the best treatment modalities. This study evaluates the efficacy and safety of minoxidil 5% topical foam in male pattern hair loss treatment and patient satisfaction. Methods: This study was a before-and-after trial on 17 male patients with male pattern hair loss. Subjects were instructed to apply one capful (1 ml) of minoxidil 5% topical foam on the scalp daily for 6 months. Efficacy was asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
0
5
0
1
Order By: Relevance
“…Minoxidil crystals cause pruritus, rash, dandruff, and allergic contact dermatitis, which greatly reduce patient comfort and lead to low compliance [ 7 , 13 ]. This prompted the creation of many non-alcohol-based minoxidil formulations that were devoid of these cutaneous side effects [ 2 , 8 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Minoxidil crystals cause pruritus, rash, dandruff, and allergic contact dermatitis, which greatly reduce patient comfort and lead to low compliance [ 7 , 13 ]. This prompted the creation of many non-alcohol-based minoxidil formulations that were devoid of these cutaneous side effects [ 2 , 8 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Good compliance due to a once-daily oral regimen. Cessation of therapy leads to the loss of observed results [19] and the reversal of any side effects that may have occurred [3].…”
Section: Finasteridementioning
confidence: 99%
“…Minoxidil: Topical minoxidil (2% or 5%) was the first FDA-approved drug for the treatment of AGA. It is available as a topical solution as well as foam preparation; however, the foam preparation is associated with lesser local reactions such as erythema or pruritus as per Hasanzadeh et al [ 19 ]. Multiple studies have reported that combination therapy is more efficacious than 5% topical minoxidil alone.…”
Section: Reviewmentioning
confidence: 99%
“…Moreover, foaming allows to transform a liquid into a spreadable formulation for easier application to, e.g., the legs. In recent years, foam formulations have established themselves as important therapy options for a multitude of indications, such as androgenic alopecia [6] and even non-dermatological conditions such as ulcerative colitis [7] or vaginal infections [8].…”
Section: Introductionmentioning
confidence: 99%